Single Daily Activity or Exercise Capacity Measurements Did not Predict Future Changes in Cardiovascular Risk Factors in Congenital Heart Disease - Jan Müller; Pia von Korn; Nils Olson; Eva Nuspl; Julia Hock; Peter Ewert; Renate Oberhoffer; Alfred Hager (Journal of Hypertension and Cardiology, 2017)
Objective: Studies suggest that cardiovascular risk of patients with congenital heart disease (CHD) is increased. This study aims on the predictive value of a single daily activity and exercise capacity assessments on the change of body-mass-index (BMI) and blood pressure in the future. Patients and Methods: We retrospectively analyzed all patients with CHD who underwent a daily activity assessment by triaxial accelerometry and accompanied cardiopulmonary exercise testing. From 276 patients 16 years or older (120 female, 28.6 ± 8.5 years) current BMI and blood pressure could be abstracted from their last outpatient visit. Results: After a mean follow-up of 5.5 ± 1.5 years, the BMI of the patients has increased from 23.0 ± 3.4 to 23.7 ± 3.5 kg/m2 (p<.001) corresponding to an annual increase of 0.14 ± 0.40 kg/m2 respectively. The systolic blood pressure decreased by -0.37 ± 3.14 mmHg (p=.049). The multivariable regression analysis corrected for confounders showed no association to annual BMI change according to baseline daily activity levels (p=.891) or peak oxygen uptake (p=.596). Only in patients with higher BMI at baseline (Beta= -.275; p<.001) and females (Beta= -.177; p=.009) increase in BMI was less. Also the blood pressure change was not associated with daily activity levels (p=.420) and peak oxygen uptake (p=.732) at baseline. Conclusions: Single daily activity or exercise capacity measures do not predict future BMI or blood pressure changes. Regular evaluation of functional status including exercise testing, activity assessment and tailored counseling are therefore recommended in patients with CHD.
Keywords: Congenital Heart Disease